Dampness, mould, onset and remission of adult respiratory symptoms, asthma and rhinitis. Issue 5 (23rd May 2019) - Wang, Juan; Pindus, Mihkel; Janson, Christer; Sigsgaard, Torben; Kim, Jeong-Lim; Holm, Mathias; Sommar, Johan; Orru, Hans; Gislason, Thorarinn; Johannessen, Ane; Bertelsen, Randi J.; Norbäck, Dan
Study question: Is dampness and indoor mould associated with onset and remission of respiratory symptoms, asthma and rhinitis among adults? Materials and methods: Associations between dampness, mould and mould odour at home and at work and respiratory health were investigated in a cohort of 11 506 adults from Iceland, Norway, Sweden, Denmark and Estonia. They answered a questionnaire at baseline and 10 years later, with questions on respiratory health, home and work environment. Results: Baseline water damage, floor dampness, mould and mould odour at home were associated with onset of respiratory symptoms and asthma (OR 1.23–2.24). Dampness at home during follow-up was associated with onset of respiratory symptoms, asthma and rhinitis (OR 1.21–1.52). Dampness at work during follow-up was associated with onset of respiratory symptoms, asthma and rhinitis (OR 1.31–1.50). Combined dampness at home and at work increased the risk of onset of respiratory symptoms and rhinitis. Dampness and mould at home and at work decreased remission of respiratory symptoms and rhinitis. The answer to the question: Dampness and mould at home and at work can increase onset of respiratory symptoms, asthma and rhinitis, and decrease remission. Dampness and mould at home and in the workplace can increase onset and decrease remission of respiratory symptoms, doctor-diagnosed asthma and rhinitis among adults. Our study adds new evidence on the health significance of dampness and mould. http://ow.ly/Ek1330o3IBn